Evaluación de residuos de antibióticos en quesillos comercializados en la ciudad de Loja - Burneo Escobar, Camilo Gabriel (2023)
Quesillo is one of the most consumed products in Ecuador. Owing to its high nutritional value, it is consumed in different ways in various dishes and even directly. Therefore, it should be free of residual drugs because their presence constitutes a serious problem for public health. This study aimed to determine the presence of antibiotic residues in cheese whey sold in the public and farmer´s markets of Loja. The research was of a qualitative observational type in which 56 samples of quesillo were collected from public and farmer´s markets. An enzyme immunoassay method "TriSensor" was used to detect the presence of Betalactams, Tetracyclines, and Sulfonamides. Forty-six positive samples were observed 79.90% of which 61.7% corresponded to market outlets and 92.71% to farmer´s markets and contained antibiotic residues corresponding to Tetracyclines. Therefore, there are residual drugs in the cheese sold, and it is suggested that research be conducted to determine the origin of the product. Keywords: Antibiotic residues, Tetracyclines, whey, cheese, public health.